Real-time versus day-ahead market power in a hydro-based electricity market - Thomas P. Tangerås; Johannes Mauritzen (Research Institute of Industrial Economics (IFN), 2014)
We analyse in a theoretical framework the link between real-time and day-ahead market performance in a hydro-based and imperfectly competitive wholesale electricity market. Theoretical predictions of the model are tested on data from the Nordic power exchange, Nord Pool Spot (NPS).We reject the hypothesis that prices at NPS were at their competitive levels throughout the period under examination. The empirical approach uses equilibrium prices and quantities and does not rely on bid data nor on estimation of demand or marginal cost functions.
Keywords: D43; D92; L13; L94; Q41; 330; Hydro power; market power; Nord Pool Spot